POG11 A novel mutation in the nerve-specific 5′-UTR of the Cx32 gene causing CMTX1. Issue 11 (22nd October 2010) - Murphy, S; Brandner, S; Polke, J; Manji, H; Houlden, H; Reilly, M M
Abstract : CMTX1 is the second most common cause of Charcot-Marie-Tooth disease (CMT), usually caused by mutations in the Cx32 gene. Cx32 has two tissue-specific promoters: P1, specific for liver and pancreas, and P2 which is nerve specific. Over 300 mutations have been described in Cx32, spread throughout the coding region. However, 10% of CMTX1 families do not have mutations in the coding region. To date, 5 noncoding region mutations have been reported. We describe two families with X-linked inheritance and a phenotype consistent with CMTX1 who did not have mutations in the Cx32 coding region. Family 1 were negative for mutations in PMP22, MPZ, SPTLC1 and GDAP1 Family 2 were negative for mutations in MPZ and rearrangements at chromosome 17p11.2. The noncoding region of Cx32 was sequenced and an upstream exon-splicing variant found at c.-373G>A which segregated with the disease in both families. This variant is located at the last base of the nerve-specific 5′UTR exon and thus may disrupt splicing of the nerve-specific transcript. Online consensus splice-site programs predict a reduced score for the mutant sequence vs the normal sequence. Two other mutations have previously been described within the 5′UTR region, which created a potential donor splice site and were shown to prevent translation of mutant mRNA. It is likely that other mutations within the Cx32 noncoding regions account for the CMTX1 families who do not have coding region mutations.